(untitled) (Bangladesh Journal of Pharmacology, 2013)
Spirulina, a dietary supplement, improves the symptoms of arsenical palmer keratosis. To understand its mechanism of action, palm skin extracts of moderate palmer arsenical keratosis (n=10), arsenic exposed controls (n=10) and healthy volunteers (n=10) were collected before and after treatment with spirulina powder 10 g/day orally for 12 weeks. The mean (±SD) amount of zinc in the palm skin of healthy volunteers was 13.1 ± 5.7 ng/cm2, which was not changed significantly in patients (11.3 ± 5.3 ng/cm2). The amount of vitamin E in healthy volunteers was 6.0 ± 0.3 ng/cm2 which was severely reduced in patients (3.5 ± 0.6 ng/cm2). The amount of linoleic acid was lowered in patient (26.7 ± 17.1 ng/cm2) which was statistically significant in comparison to healthy volunteers (p=0.029). After supplementation of spirulina, zinc level in the palm skin of arsenic exposed controls was increased but it was not statistically significant (p=0.068). The vitamin E and linoleic acid levels were not changed significantly in the skin of palm. In conclusion, arsenical keratosis showed significantly low levels of vitamin E and linoleic acid without any significant change in zinc level. After supplementation of spirulina, low levels of these three compounds were not returned towards the normal levels.